2018
DOI: 10.1002/rcs.1891
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted coronary artery bypass surgery: an 18‐year single‐centre experience

Abstract: Robot-assisted coronary artery bypass grafting is safe, feasible and it seems to represent an effective alternative to traditional coronary artery bypass grafting in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Postoperative angiogram was performed in 599 patients with early graft patency of 97.4%. 6 In the early 2000s, hybrid coronary revascularization, which combines surgical LIMA-LAD bypass with PCI, emerged as an alternative treatment option for multivessel coronary artery disease. In the hybrid procedure, the surgical graft could be routinely evaluated at the time of PCI.…”
Section: Early Graft Patency After Rmidcabmentioning
confidence: 99%
“…Postoperative angiogram was performed in 599 patients with early graft patency of 97.4%. 6 In the early 2000s, hybrid coronary revascularization, which combines surgical LIMA-LAD bypass with PCI, emerged as an alternative treatment option for multivessel coronary artery disease. In the hybrid procedure, the surgical graft could be routinely evaluated at the time of PCI.…”
Section: Early Graft Patency After Rmidcabmentioning
confidence: 99%
“…The benefits of robotic cardiac surgery have been established and amply described . Robotic cardiac surgery allows for excellent visualization of intra and epicardial structures.…”
Section: Discussionmentioning
confidence: 99%
“…82 This low prevalence is largely owing to the absence of large randomized control trials demonstrating its long-term safety or superiority over conventional CABG, although trials have suggested its safety and cost-effectiveness. 84,85 Further barriers to the dissemination of robotic technology in this setting include the initial high equipment cost, a significant learning curve and a relatively longer operating time. 82,83 A recent trial evaluated a single-center experience of robotic coronary artery bypass grafting over 18 years (1998-2016).…”
Section: Robotic Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…82,83 A recent trial evaluated a single-center experience of robotic coronary artery bypass grafting over 18 years (1998-2016). 84 The cohort size was 605 with a reported operative mortality of 0.3%. The learning curve is reflected in the observation that after the first 200 cases, the conversion rate to sternotomy fell from 16% to 6.9%.…”
Section: Robotic Coronary Artery Bypass Graftingmentioning
confidence: 99%
See 1 more Smart Citation